2017
DOI: 10.1016/j.ijproman.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of megaproject environmental responsibility on organizational citizenship behaviors for the environment: A social identity perspective

Abstract: The importance of organizational citizenship behaviors for the environment (OCBEs) has been clearly established in the environmental literature. However, the OCBEs construct has rarely been examined in the specific and increasingly important realm of megaproject environmental responsibility (MER). To fill this gap, this paper presents an individual-level analysis that explores the impact of project participants' perceptions of MER practices on their environmental commitment and OCBEs. The results show that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 58 publications
1
79
0
2
Order By: Relevance
“…e earliest theory of action and the farreaching theory of rational behavior demonstrate a direct relationship between cognition and behavior [44,45]. Scholars who study CSR empirically showed that SRC is positively correlated with social responsibility behavior [46,47].…”
Section: Src and Msrbmentioning
confidence: 99%
See 3 more Smart Citations
“…e earliest theory of action and the farreaching theory of rational behavior demonstrate a direct relationship between cognition and behavior [44,45]. Scholars who study CSR empirically showed that SRC is positively correlated with social responsibility behavior [46,47].…”
Section: Src and Msrbmentioning
confidence: 99%
“…In contrast with other units, such as survey and design, the MSR issues faced by owners, governments, and contractors are becoming complicated. is study used one-way analysis of variance (ANOVA) to test the two variables of HB and SB among different participating organizations to test the problem considering that differences in the choice of social responsibility behaviors for project roles may be observed [47]. e results indicate no significant difference (P value is 0.203 and 0.571, both values are greater than 0.05).…”
Section: Sample and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los resultados muestran que las percepciones de los participantes del proyecto sobre las prácticas de RAM dirigidas a los interesados internos (vinculados en contratos del proyecto) están relacionadas de manera positiva con sus CCOA. Por el contrario, las percepciones de los participantes del proyecto de las prácticas de RAM dirigidas a los interesados externos (la comunidad local y el público en general) tienen un impacto insignificante en sus CCOA (Wang et al, 2017). Una nueva línea de trabajo se enfoca en la necesidad de desarrollar una identidad ambiental fuerte que involucre a toda la organización.…”
Section: Responsabilidad Corporativaunclassified